Mendidik Anak Takut Akan Tuhan - Muara Sinaga (Jurnal Euangelion, 2021)
Abstract: Parents have an important role in fostering children, parents are role models for children in acting in their behavior. Parents play an important role in nurturing children to fear God, love children, educate children to be smart, instill right living, instill a life of justice, instill honest life, nurture children to be smart, instill a wise life, instill a considerate life. Fear of God can lead a person (child) to experience renewal in terms of attitude or behavior to experience renewal of mind. Those who fear the LORD will do His word. Understanding the true concept of fearing God in Proverbs 1:7 can be the basis for parents to educate children in the family. Keywords: educate, proverbs, fear of God     Abstrak: Orang tua memiliki peranan penting dalam membina anak, orangtua menjadi panutan bagi anak dalam bertindak dalam perilakunya. Orang tua berperan penting dalam membina anak untuk takut akan Tuhan, mengasihi anak, mendidik anak agar pandai, menanamkan hidup benar, menanamkan hidup keadilan, menanamkan hidup jujur, membina anak agar cerdas, menanamkan hidup bijaksana, menanamkan hidup yang penuh pertimbangan. Takut akan Tuhan dapat mengarahkan seseorang (anak) mengalami pembaharuan dari segi sikap atau tingkah laku mengalami pembaharuan akal budi. Orang yang takut akan TUHAN akan melakukan firman-Nya. Memahami konsep takut akan Tuhan yang benar dalam Amsal 1:7 dapat menjadi dasar bagi orang tua untuk mendidik anak di dalam keluarga. Kata Kunci: mendidik, amsal, takut akan Tuhan,